2020
DOI: 10.1038/s41598-020-68479-0
|View full text |Cite
|
Sign up to set email alerts
|

Foliar application of specific yeast derivative enhances anthocyanins accumulation and gene expression in Sangiovese cv (Vitis vinifera L.)

Abstract: The effect of elicitors on secondary metabolism in vines is receiving much interest, since it has been shown that they are able to increase the accumulation of phenolics, especially anthocyanins. This research aims to investigate the biochemical and molecular effects of the application of a commercial yeast derivative ( Saccharomyces cerevisiae ) on the accumulation of anthocyanins in potted Sangiovese vines. Experiments were performed on three consecutive years and the yeast derivative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 66 publications
1
10
0
Order By: Relevance
“…Total anthocyanins were found to be higher in 2016 than in 2017 (1083.3 versus 764.7 mg kg −1 ), whereas, between the two crop levels, their content was more abundant in the thinning trial (822.0 versus 1025.7 mg kg −1 ), showing a significant effect of the interaction for both factors Y and CL. Grapes were mainly characterized by the non-acylated form of the five anthocyanins according to Pastore et al 28 and were found in the follow order of abundance: malvidin-3-glucoside ≈ peonidin-3-glucoside > cyanidin-3-glucoside > petunidin-3-glucoside > delphinidin-3-glucoside. Season and thinning practice influenced the composition of anthocyanins.…”
Section: Resultsmentioning
confidence: 99%
“…Total anthocyanins were found to be higher in 2016 than in 2017 (1083.3 versus 764.7 mg kg −1 ), whereas, between the two crop levels, their content was more abundant in the thinning trial (822.0 versus 1025.7 mg kg −1 ), showing a significant effect of the interaction for both factors Y and CL. Grapes were mainly characterized by the non-acylated form of the five anthocyanins according to Pastore et al 28 and were found in the follow order of abundance: malvidin-3-glucoside ≈ peonidin-3-glucoside > cyanidin-3-glucoside > petunidin-3-glucoside > delphinidin-3-glucoside. Season and thinning practice influenced the composition of anthocyanins.…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, BSTC treated AlHama cv recorded maximum increases in vegetative growth, as the yield increased more than double increased and plant height increased 50% compared to the Moraleda cv, that may be due to change in the genetic background between the two cvs which may act different with the foliar fertilizers. There is evidence that nutrient supply from the YE increase growth parameters in date palm 37 , soybean 38 , grape 20 , sweet potato 39 , pea 40 and snap bean 41 . Several bioactive compounds were used as plant growth regulators to enhance crop quality such as salicylic acid, nitric oxide, jasmonic acid, ascorbic acid and citric acid were used to improve the immunity, yield and quality of various crops 42 .…”
Section: Resultsmentioning
confidence: 99%
“…In addition, Antioxidants and plant growth promoting compounds such as nitrogen components, salicylic acid (SA), ascorbic acid, etc. have been used as stimulators for increasing the yield and quality of crops and fruits 20 , 21 .…”
Section: Introductionmentioning
confidence: 99%
“…Elicitors are one of the most commonly used strategies to increase secondary metabolite content in berries. Previous studies indicated that elicitors stimulate an "immune-like" response in grapes, triggering the production and accumulation of compounds such as polyphenols, phytoalexins, stilbenes, anthocyanins, and tannins [5,9,14]. Inactive dry yeast extracts (DYE) are a group of elicitors that can induce the accumulation of phenols, terpenoids, and other aromatic compounds [5,14].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies indicated that elicitors stimulate an "immune-like" response in grapes, triggering the production and accumulation of compounds such as polyphenols, phytoalexins, stilbenes, anthocyanins, and tannins [5,9,14]. Inactive dry yeast extracts (DYE) are a group of elicitors that can induce the accumulation of phenols, terpenoids, and other aromatic compounds [5,14]. Thus, DYE treatments are gaining interest as tools that can be exploited in organically managed vineyards to enhance the aroma profile of white grape varieties in the presence of unfavorable climatic conditions.…”
Section: Introductionmentioning
confidence: 99%